ICD implantation in left ventricular noncompaction: A case report and review of the literature - (:unkn) unknown (VIA MEDICA, 2011)
Left ventricular noncompaction (LVNC) is an uncommon cardiomyopathy characterized by the persistence of fetal myocardium with a pattern of prominent trabecular meshwork and deep intertrabecular recesses, systolic dysfunction and left ventricular dilatation. It is thought to be caused by the arrest of normal endomyocardial morphogenesis. There is no consensus on the definition, diagnostic criteria, pathogenesis or treatment of LVNC. We report the case of a 43 year-old patient with LVNC, nonsustained ventricular tachycardia and family history of sudden cardiac death (SCD). An implantable cardioverter-defibrillator (ICD) was prophylactically implanted because of the individual's high SCD risk. Although ICD is an effective option for preventing SCD, data on the long-term follow-up of patients with LVNC is limited. (Cardiol J 2011; 18,6:691-694)
Keywords: left ventricular noncompaction; implantable cardioverter-defibrillator; ventricular tachycardia; heart failure; arrhythmia; NON-COMPACTION; MYOCARDIUM